The Morphometric characteristics of otoliths of Ophichthus remiger from the fishery on the Ecuadorian coast (Revista Científica Ciencias Naturales y Ambientales, 2018)
The common eel (Ophichthus remiger) is a species of commercial value, of which, the biologicalfishing aspects as the biometric relations are poorly known. The aim of this work was to determine the morphometric characteristics of the common eel in Ecuador as the otoliths and the correlation of those with the size and weight. Size data of this species collected by the Instituto Nacional de Pesca were analyzed at the landing ports of Manta, Anconcito and Posorja, and 241 pairs of otoliths were extracted from samples at those sites. The sizes (length and width) and the weight of otoliths were compared between the left and right side of males and females and between those by analysis of variance of a factor (ANOVA) and multivariate (MANOVA). Linear regressions between sizes and weights of otoliths correlated to the total length of organisms were performed. No significant differences were found between left and right side otoliths in each sex (p> 0.05); however, differences among males and females (p
Keywords: Allometry; biometric relationships; common eel; retro-calculus